Is Local Nitric Oxide Availability Responsible for Myocardial Salvage after Remote Preconditioning? - Arroyo-Martínez,Esbeidira Aranet (2016)
Abstract Background: Remote ischemic preconditioning (RIPC) represents an attractive therapy for myocardial protection, particularly when ischemic events can be anticipated. Although several hypothetic mechanisms have been proposed, no definite molecular pathways have been elucidated. Objective: We evaluated the effect of brachial circulation cuff occlusion on myocardial ischemic tolerance, necrosis, and nitric oxide (NO) in patients with ischemic heart disease undergoing elective percutaneous coronary interventions (PCI). Methods: 46 patients were randomly allocated into two groups: control and RIPC before PCI procedures. Electrocardiographic analysis, serum concentrations of troponin I (cTn-I) were measured at baseline and 24 hours after PCI. A blood sample from the atherosclerotic plaque was drawn to determine nitrate and nitrites. Results: RIPC increased the availability of NO in the stented coronary artery. Control patients presented a small but significant increase in cTn-I, whilst it remained unchanged in preconditioned group. The preconditioning maneuver not only preserved but also enhanced the sum of R waves. Conclusions: RIPC induced an intracoronary increase of NO levels associated with a decrease in myocardial damage (measured as no increase in cTn-I) with electrocardiographic increases in the sum of R waves, suggesting an improved myocardium after elective PCI.